Evaluation of a Tumor-Targeting, Near-Infrared Fluorescent Peptide for Early Detection and Endoscopic Resection of Polyps in a Rat Model of Colorectal Cancer - Jade E. Jones BHS; Susheel Bhanu Busi MS; Jonathan B. Mitchem MD; James M. Amos-Landgraf PhD; Michael R. Lewis PhD (Molecular Imaging)
The goal of these studies was to use a tumor-targeting, near-infrared (NIR) fluorescent peptide to evaluate early detection and to guide surgical removal of polyps in a genetically engineered rat model of spontaneous colorectal cancer. This peptide, LS301, was conjugated to Cy7.5 and applied topically to the colon of adenoma-bearing Pirc rats. Ten minutes after administration, rats underwent targeted NIR laser colonoscopy. Rats were also evaluated by white light colonoscopy and narrow-band imaging, for comparison to the NIR technique. Unlike white light and narrow-band colonoscopy, NIR imaging detected unexpected flat lesions in young Pirc rats. NIR imaging was also used to assess resection margins after electrocauterization of polyps. Tumor margins remained negative at 5 weeks postsurgery, demonstrating successful polypectomy. The present studies show that NIR-targeted colonoscopy is an attractive strategy to improve screening for and resection of colorectal neoplasia.